2002
DOI: 10.1159/000053316
|View full text |Cite
|
Sign up to set email alerts
|

How Do We Organize Smooth, Effective Transfer from Paediatric to Adult Diabetes Care?

Abstract: Transition from paediatric to adult care is a major milestone in the life of a young person with diabetes, yet it is commonly poorly done. This finding is supported by the dearth of publications in the literature that particularly relate to transition in diabetes care. Other transitions occur at this time of life, for example: from parental supervision to growing independence and from secondary school to post-school options. Health professionals know, from anecdotal evidence, that this is the period when young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 1 publication
1
27
0
5
Order By: Relevance
“…Patients who required medical attention following discharge from pediatric care could not access it even when they experienced flares or ran out of medication. This replicates findings in transition cohorts of patients with sickle cell anemia (17) and diabetes mellitus (44), in which issues surrounding health insurance featured prominently. Maximizing accessibility to health care may diminish the financial difficulties surrounding transition and impact medical outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…Patients who required medical attention following discharge from pediatric care could not access it even when they experienced flares or ran out of medication. This replicates findings in transition cohorts of patients with sickle cell anemia (17) and diabetes mellitus (44), in which issues surrounding health insurance featured prominently. Maximizing accessibility to health care may diminish the financial difficulties surrounding transition and impact medical outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…The HbA1c of the ‘drop-outs’ was higher than the average HbA1c prior to the transfer. Health professionals know, from anecdotal evidence, that this is the period when young people ‘drop out’ of the system or rarely visit a specialist [7,8,9,10,11, 23]. Bartsch et al[ 22] reported that 10% (n = 96, 18.9 years old) of the patients interviewed after transfer didn’t see a doctor and 24% never or less than once a year saw a physician.…”
Section: Discussionmentioning
confidence: 99%
“…The individual rather than the family approach or busy clinics full of elderly sick patients are often alienating for the young adult [7, 8]. Previous studies have shown that some patients drop out of the medical care system or their attendance rate decreases with consequent deterioration of metabolic control [9,10,11]. Therefore, effective care needs to encompass the various psychological, social and educational factors.…”
Section: Introductionmentioning
confidence: 99%
“…Occurring often at the same time as other important steps of life (i.e. leaving the family to live independently, leaving or changing school, and starting work), transition may cause problems for young adults and their families (Schidlow and Fiel 1990;Callahan et al 2001;McGill 2002;Feillet et al 2010). The young adults have to deal with their own responsibilities in the adult outpatient clinic and they are forced to show personal initiative and independence in handling their disease.…”
mentioning
confidence: 99%